2010
DOI: 10.1007/s10658-010-9617-x
|View full text |Cite
|
Sign up to set email alerts
|

An integrated multivariate approach to net blotch of barley: Virulence quantification, pathotyping and a breeding strategy for disease resistance

Abstract: Knowledge of pathotype diversity and virulence in local populations of Pyrenophora teres is a prerequisite to screening for durable resistance to net blotch. The current study aimed to quantify the virulence level of Moroccan isolates, identify and designate existing pathotypes, and select resistant genotypes. We developed a method for virulence quantification of P. teres isolates based on a conversion of infection responses into frequencies for use in correspondence analysis. Coordinates of the first axis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…In contrast, in our study we recorded 5.8 IR for Rabat071. Similarly, Rabat071 was reported to be resistant with a mean IR of 3.4 when challenged with 61 Moroccan Ptt isolates collected during the field survey of (Jebbouj and El Yousfi 2010. In our study, however, Rabat071 was one of the most susceptible genotype (susceptible to 11 out of 15 Ptt isolates).…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…In contrast, in our study we recorded 5.8 IR for Rabat071. Similarly, Rabat071 was reported to be resistant with a mean IR of 3.4 when challenged with 61 Moroccan Ptt isolates collected during the field survey of (Jebbouj and El Yousfi 2010. In our study, however, Rabat071 was one of the most susceptible genotype (susceptible to 11 out of 15 Ptt isolates).…”
Section: Discussioncontrasting
confidence: 45%
“…Very recently, Bentata (2015) reported highly virulent Ptt isolates to Rabat071 and argued that dominance of these isolates in Moroccan Ptt population might lead to an epidemic of net blotch. In contrast to Jebbouj and El Yousfi (2010), during the disease survey of 2015 in Morocco, Rehman and El Yousfi (unpublished data) found that ~60% of Moroccan farmers grew Rabat071 in survey area and the disease severity of Ptt on Rabat071 was recorded between 35-75%. According to McDonald and Linde (2002), pathogens with mixed reproduction system (pathogen with both sexual and asexual Cereal Research Communications 44, 2016 cycles per growing season) pose greater threat to erosion of resistance in host.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations